2021
DOI: 10.3390/nu13010274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caloric Restriction Diet on Arterial Hypertension and Endothelial Dysfunction

Abstract: The most common manifestation of cardiovascular (CV) diseases is the presence of arterial hypertension (AH), which impacts on endothelial dysfunction. CV risk is associated with high values of systolic and diastolic blood pressure and depends on the presence of risk factors, both modifiable and not modifiable, such as overweight, obesity, physical exercise, smoking, age, family history, and gender. The main target organs affected by AH are the heart, brain, vessels, kidneys, and eye retina. AH onset can be cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 143 publications
2
27
0
7
Order By: Relevance
“…Adherence could be explained by a variety of factors, such as: (a) the type and duration of nutritional treatment received [ 37 , 38 ], highlighting the importance of follow-up to assess the efficacy of the intervention in the short and long term [ 39 , 40 ]; (b) motivation: as one of the facilitating factors in adherence to FV consumption [ 41 , 42 ], versus who was assigned to the control group; (c) access to information: adherence may be hampered due to the fact that practical aspects of the assigned intervention are unknown, such as portion sizes and the need for food variability [ 43 ]; (d) employment status and occupation: occupation gathers information on life styles and conditions related to education and income level; at a general level, a better professional qualification provides better working conditions and higher income, conditions associated with a higher prevalence of FV consumption [ 44 , 45 ]; (e) psychosocial stress: subjects with a history of cardiovascular disease undergoing a nutritional intervention [ 46 ], such as the consumption of FV according to recommendations assigned by the professional, in the long term generate allostatic load, that is, a maladaptive response, in this case not following the recommendations indicated [ 47 ]; (g) compensatory health beliefs: a factor that can influence adherence to FV consumption and consists of the belief that unhealthy behavior can be compensated; for example, eating unhealthily can be offset by exercising [ 42 ]; or, finally, (h) psychotherapeutic interventions: among psychotherapeutic interventions for modifying behaviors to promote adherence to nutritional interventions [ 48 ], we find Behavioral Activation (BA), focused on the reduction in avoidance behaviors and the development of routines and rewarding behaviors that allow greater adherence to FV consumption in adults with subsyndromal symptoms of depression [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adherence could be explained by a variety of factors, such as: (a) the type and duration of nutritional treatment received [ 37 , 38 ], highlighting the importance of follow-up to assess the efficacy of the intervention in the short and long term [ 39 , 40 ]; (b) motivation: as one of the facilitating factors in adherence to FV consumption [ 41 , 42 ], versus who was assigned to the control group; (c) access to information: adherence may be hampered due to the fact that practical aspects of the assigned intervention are unknown, such as portion sizes and the need for food variability [ 43 ]; (d) employment status and occupation: occupation gathers information on life styles and conditions related to education and income level; at a general level, a better professional qualification provides better working conditions and higher income, conditions associated with a higher prevalence of FV consumption [ 44 , 45 ]; (e) psychosocial stress: subjects with a history of cardiovascular disease undergoing a nutritional intervention [ 46 ], such as the consumption of FV according to recommendations assigned by the professional, in the long term generate allostatic load, that is, a maladaptive response, in this case not following the recommendations indicated [ 47 ]; (g) compensatory health beliefs: a factor that can influence adherence to FV consumption and consists of the belief that unhealthy behavior can be compensated; for example, eating unhealthily can be offset by exercising [ 42 ]; or, finally, (h) psychotherapeutic interventions: among psychotherapeutic interventions for modifying behaviors to promote adherence to nutritional interventions [ 48 ], we find Behavioral Activation (BA), focused on the reduction in avoidance behaviors and the development of routines and rewarding behaviors that allow greater adherence to FV consumption in adults with subsyndromal symptoms of depression [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first therapeutic approach applied in case of MetS is the modification of eating habits and lifestyle. It is in fact known how an improvement in eating habits, with a reduction in caloric intake in the case of overweight and obesity, a reduction in the intake of sodium, saturated fats, cholesterol, and simple sugars, can help in the clinical management of MetS comorbidities [49]. In some cases, it may be necessary to resort to pharmacological therapy.…”
Section: Possible Effects Of Natural Bioactive Compounds In Metabolicmentioning
confidence: 99%
“…A recent in vitro study by Vamanu et al [305], demonstrated that Curcuma longa extract, particularly rich in curcumin, changes the gut microflora composition of hypertensive patients through the increased release of SCFAs thus, in turn, enhances the Enterobacteriaceae and decreases Bacteroidetes-Prevotella-Porphyromonas genera. Several studies speculate that the modulation of metabolic pattern producing SCFAs may represent an innovative approach to counteract pathological conditions, such as MetS, chronic kidney disease, and AH, characterized by a low-grade inflammatory status [44,45,49,74,261,306]. In this perspective, the most SCFA studied is represented by butyric acid.…”
Section: Effects Of Natural Bioactive Compounds On Gut Microbiota Metmentioning
confidence: 99%
“…Essential AH results from the interplay of genetic, environmental and behavioral factors. Among environmental and behavioral factors, dietary habits related to geographical area, culture and ethnic group play an important role [29,35,36]. Essential AH is absent in populations with very low daily sodium intake [37].…”
Section: Impact Of Western Diet On Arterial Hypertensionmentioning
confidence: 99%